Phenotypic Characterization And Spoligotype Profiles Of Mycobacterium Bovisisolated From Unpasteurized Cows’ Milk In Ibadan, Nigeria. (2007)
A pilot study was carried out to screen for the presence of Mycobactcria in unpasteurized milk from cows mcant for sale at the cattle market in the mclropolitan city of Ibadan. South-western Nigeria. Fifty three milk samplcs were cultured using 7H11 -Middlebrook media while nitrate and niaein biochemical tests were carried out initially to classify the isolated Mycobacteria specics and the results were later' confirmed by spoligotyping. In all, Mycobacterium bovis were isolated from 6 (11.3%) milk samples. The detected spoligotypes obtained were NI, N6, N9, NI6. and N28 (two isolates). After comparison with the "Mycobacterium bovis Spoligotype Database” (www.mbovis.org), spoligotypes NI. N6, and N16 were found to have been already documented (N1=SB0944; N6=SBI027: NI6=SB0951). while N9 and N28 were relative!)' new strains and undocumented. The public health implication of these findings is that humans are at great risk of exposure to infection with M. bovis through the consumption of unpasteurized milk from cattle through the food chain.